2008
DOI: 10.1111/j.1095-8339.2008.00785.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential refugium on the Qinghai–Tibet Plateau revealed by the chloroplast DNA phylogeography of the alpine species Metagentiana striata (Gentianaceae)

Abstract: Metagentiana striata is an alpine annual herbaceous plant endemic to the east of the Qinghai-Tibet (Q-T) Plateau and adjacent areas. The phylogeography of M. striata was studied by sequencing the chloroplast DNA (cpDNA) trnS-trnG intergenic spacer. Ten haplotypes were identified from an investigation of 232 individuals of M. striata from 14 populations covering the entire geographical range of this species. The level of differentiation amongst populations was very high (GST = 0.746; NST = 0.774) and a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
90
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(108 citation statements)
references
References 72 publications
16
90
2
Order By: Relevance
“…This conclusion is supported by the unimodal mismatch distribution of the northeastern populations (Figure 4a), suggesting historical population expansion, and by the star-shaped phylogeny of haplotypes derived from haplotype A (Figure 2), the reduced levels of haplotypic and nucleotide diversity (Table 1), and the prevalence of haplotype A in the northeastern populations (Figure 1). The homogeneous genetic pattern in the northeastern populations is consistent with the AMOVA result, which showed relatively low genetic variation among populations (48.7%) in comparison with other alpine plant species on the Plateau (Chen et al, 2008;Yang et al, 2008;Wang et al, 2009). These patterns are consistent with the results of a simulation study in which sudden expansion from a few populations produced reduced allele diversity and areas of genetic homogeneity (Avise, 2000).…”
Section: A Shimono Et Alsupporting
confidence: 80%
See 2 more Smart Citations
“…This conclusion is supported by the unimodal mismatch distribution of the northeastern populations (Figure 4a), suggesting historical population expansion, and by the star-shaped phylogeny of haplotypes derived from haplotype A (Figure 2), the reduced levels of haplotypic and nucleotide diversity (Table 1), and the prevalence of haplotype A in the northeastern populations (Figure 1). The homogeneous genetic pattern in the northeastern populations is consistent with the AMOVA result, which showed relatively low genetic variation among populations (48.7%) in comparison with other alpine plant species on the Plateau (Chen et al, 2008;Yang et al, 2008;Wang et al, 2009). These patterns are consistent with the results of a simulation study in which sudden expansion from a few populations produced reduced allele diversity and areas of genetic homogeneity (Avise, 2000).…”
Section: A Shimono Et Alsupporting
confidence: 80%
“…Wang et al (2009) suggested that Aconitum gymnandrum has survived on high-altitude parts of the central Plateau throughout the Quaternary. In contrast, Metagentiana striata and Pedicularis longiflora probably expanded from refugia on the eastern edge to the central Plateau during the interglacial and postglacial periods (Chen et al, 2008;Yang et al, 2008). Therefore, these three investigated alpine species do not share a common phylogeographical history.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recent range expansion from the 'hot spot' of the mountains of the southeastern TP has been observed in other plants and birds at the population level. Examples include Juniperus przewalskii (Cupressaceae) , Metagentiana striata (Gentianaceae) (Chen et al, 2008), Pedicularis longiflora (Orobanchaceae) (Yang et al, 2008), Picea crassifolia (Pinaceae) (Meng et al, 2007), and the red-necked snow finch Pyrgilauda ruficollis (Qu et al, 2005). Phylogeographic studies on these species show that populations from the wide range of the platform are dominated by one or a few haplotypes and are mostly nested within diverse haplotypes from the southeastern mountains of the TP.…”
Section: Biogeographic Diversification On the Tibetan Plateaumentioning
confidence: 99%
“…In contrast, studies on the Asian biota have been rather limited. The complex topography of East Asia probably provided refugia for species during times of Pleistocene glaciation [14], yet only a few plant and bird species restricted to the Qinghai-Tibetan Plateau (QTP) have been evaluated [15][16][17][18][19][20].…”
mentioning
confidence: 99%